Professional Development of Excellent Physics Teachers - Liu, Tingting; Sun, Haibin (Professional Development of Outstanding Physics Teachers, 2023)
Excellent teacher is a representative in the teacher group and is the decisive force to boost innovation and development of education and teaching. The level of teachers’ professional development can be characterized by the theory of teacher professional development status. The quality of teaching and research papers published by teachers can directly reflect the professional development level of teachers. Based on the bibliometric analysis of CNKI in 2010-2019, the situation of teaching and research papers published by middle school physics teachers in Shandong Province in the past ten years was analyzed, and visual analysis was performed using Citespace software. The excellent senior high school physics teachers’ professional growth actuality is surveyed by the self-made “Questionnaire of Excellent Senior High School Physics Teachers’ Professional Growth”, and by the survey, the total status and the professional growth of excellent senior high school physics teachers could be grasped.